Фольклор спротиву в культурній традиції українців - Лихограй, Роман Володимирович (Київський національний університет імені Тараса Шевченка, 2017)
Ідеться про традиційні українські цінності та уявлення, представлені в різночасових фольклорних текстах про спротив окупації. Наскрізною є теза про генетичний зв'язок жанрів цього пласту народної творчості.

The article deals with traditional Ukrainian values and conceptions presented in folklore texts on resistance of different time. The thesis about genetic links between the genres of this part of folk art is transparent.
Resistance folklore in the cultural tradition of the ukrainians
Keywords: фольклор спротиву; фольклор Майдану; козацькі пісні; стрілецькі пісні; повстанські пісні; folklore resistance; folklore of the Maidan; Cossack songs; rifle songs; rebel songs